Analysis and modeling of calendar aging of a commercial LiFePO4/graphite cell. (June 2018) - Naumann, Maik; Schimpe, Michael; Keil, Peter; Hesse, Holger C.; Jossen, Andreas
Highlights: First aging study for widely commercially used LFP/graphite cell from Sony. Analysis of aging influence of temperature and SOC by 17 test points over 885 days. Semi-empirical model to estimate aging of cell capacity and resistance. Model validation with additional dynamic aging study based on 15 test points. Abstract: This paper presents a comprehensive calendar aging study on a lithium-ion battery with a test duration of 29 months. This aging study was realized with a widely used commercial LiFePO4 /graphite cell from Sony/Murata, which promises both long calendar and cycle lifetime, which is especially required for stationary battery applications. The development of the cells' capacity, as well as the resistances, are shown in a static calendar aging study for 17 test points, each with 3 cells, having constant storage conditions of temperature and state of charge. Based on the measurement data, a semi-empirical aging model is presented for the capacity loss and resistance increase, consisting of only 5 parameters which are valid for all storage conditions. An additional dynamic calendar aging study is performed with 9 months test duration for model validation, consisting of 15 test points with varying conditions of temperature and state of charge. The absolute model errors against the validation data points remain below 2.2% for the capacity loss and below 6.9% for the resistance increase for all dynamic validation tests. In conclusion, this calendar aging model allows the prognosis of the calendar lifetime of LiFePO4 /graphite batteries in different applications with varying storage conditions over time.